Physiological and physiopathological modulation of GPER1 in the reproductive system of the Wistar rat and the sand rat - FERNINI Meriem (Université de Mostaganem, 2025)
The journey of research in reproductive physiology, infertility, and cancer, requires deep understanding of GPER1 pathway to promotes estrogenic effects in the male reproductive physiology. GPER1 mediates several intracellular pathways leading to various physiological effects. While free-ranging animals, having a seasonal reproductive cycle, seem to be the perfect animal models to perform such studies. Our work aimed in the first part to investigate GPER1 localisation in the reproductive system of the sand rat ( Psammomys obesus) and the gerbil (Gerbillus gerbillus), seasonally breeding rodents from North Africa, employing immunohistochemical approach. In the second part, in silico approach was used to clarify the interaction between different endocrine disrupting chemicals, phytochemicals and known ligands with the GPER1. The histology of the testis, the efferent ducts and the epididymis of both rodents underwent remarkable alterations during the resting season. The expression of the GPER1 during the breeding season, was found all over the testis, the efferent ducts, and the epididymis. While during the resting season, we noticed the absence of the GPER1 in Sertoli cells and spermatogonia, but it was found in the Leydig cells and spermatocytes, as spermatogenesis was blocked at the stage of spermatocytes. In the efferent ducts, not all ciliated cells, non-ciliated cells and basal cells were immunostained, while in the epididymis, only principal cells and basal cells expressed GPER1. Interestingly, the endocrine disruptors showed the highest affinity among the tested substances, for instance, Bisphenol A, Polychlorinated Biphenyls and Acrylamide had G of -16.47 kcal/mol, -10.35 kcal/mol and -8.78 kcal/mol respectively. While phytochemicals that had lower binding energies were Coumestrol with G of -9.03 kcal/mol, Genistein with G of -8.47 kcal/mol and Biochanin A with G of -8.33 kcal/mol. In addition, Estramustin, a chemotherapeutic agent derived from oestrogen displayed low binding energy G of -7.45 kcal/mol. In summary, the presence of GPER1 in the breeding season and its absence during the resting season signal the influence of the seasonal fluctuations on estrogenic actions via GPER1 and highlight the importance of the GPER1 in normal reproductive physiology of the male. Nevertheless, the low binding energies and the high affinity displayed by endocrine disruptors witness their emerging effects on endocrine system and the need to supervise the use of these harmful chemicals. Furthermore, the strong interactions between phytochemicals and Estramustin chemotherapeutic agent with the GPER1 advocate the possibility of using these chemicals as therapeutic agents targeting the GPER1 in several types of pathologies prompted by the GPER1.
Keywords: GPER1; testis; efferent ducts; epididymis; oestrogen; phytochemicals; endocrine disruptors.